Endoscopic Management of Primary Obstructive Megaureter: Review of 28 Consecutive Cases (Medical Forum Monthly, 2024)
Objective: To determine the importance of endoscopic dilatation in the management of primary obstructive megaureter.Study Design: Cross sectional studyPlace and Duration of Study: This was conducted at Institute of kidney Diseases Peshawar, Pakistan from July 2017 to June 2018.Materials and Methods: A sample of 28 patients was selected by convenience sampling. Detail history, examination, urinalysis and complete blood count, ultrasonography and MAG3 renography were performed in all patients. Age in months was a ratio data and analyzed for mean, SD, minimum and maximum.Results: The age range was 4 months to 144 months. The mean age was 26months+5.4SD. Male to female ratio was 1.8. Range of Distal ureter diameter on Ultrasound was 9 to 35 mm with average of 14mm+6.85SD. Preoperative diuretic MAG3 showed obstruction in all cases with split renal function with range of 18 to 35% on affected side.JJ stent duration was 3 to 12 weeks with Average9 weeks+4.29SD.Reflux was not noted in any patient on postoperative MCUG.Conclusion: Endoscopic treatment of obstructive megaureter is practical and effective therapeutic option. It should be extended to symptomatic cases for which open surgical repair is indicated.